The relationship of financial advisors' outward presentation and client acquisition of selected insurance companies in Tacloban City - Mina, Ma. Angelique M.; Morillo, Yasmin Crystha M.; Obregon, Mariel May C.; Oriondo, Yanna Alexis O. (2024)
The findings indicate a shared acknowledgment among financial advisors and insurance companies regarding the significant impact of outward presentation on client acquisition. Financial advisors recognize that their presentation plays a pivotal role in shaping initial client perceptions and influencing their decision-making process. Insurance companies, in turn, emphasize the importance of equipping advisors with the necessary skills to effectively communicate and build relationships with clients.
The study concludes that refining outward presentation skills through targeted training programs can strengthen client relationships, thereby contributing to increased insurance adoption in Tacloban City. By enhancing the professionalism and communication effectiveness of financial advisors, insurance companies can improve their client acquisition efforts and ultimately drive growth in the local insurance market.
This study investigates how financial advisors' outward presentation influences client acquisition in the Tacloban City insurance sector. Given the low insurance penetration rate in the Philippines, the role of financial advisors in expanding market reach is crucial. The study emphasizes the importance of outward presentation, which encompasses demeanor, communication style, and professionalism, in fostering trust and confidence among clients. Through qualitative methods, the research explores the perspectives of financial advisors and examines existing strategies employed by insurance companies.
Undergraduate thesis (B.S. Management) -- University of the Philippines, Tacloban.